Stillbirth: The heart of the matter. Issue 3 (23rd January 2014) - Jorgensen, Michael; McPherson, Elizabeth; Zaleski, Christina; Shivaram, Pushpa; Cold, Christopher
<x xml:space="preserve">Abstract</x> We evaluated 2, 083 cases within the Wisconsin Stillbirth Service Program (WiSSP) that had autopsy reports or ultrasound data relevant to the heart. Of these, 167/1, 782 (9.4%) stillbirths after 20 weeks and 11/301 (3.7%) miscarriages <20 weeks had congenital heart disease (CHD). Cases were classified by type of heart defect and whether it related to cause of death. Among cardiac anomalies that contributed significantly to fetal death, 125/151 (83%) were associated with underlying conditions or syndromes, nearly half of which were chromosomal. The most common forms of CHD in stillborns were severe cyanotic lesions (3%), then ventricular (2.6%) and atrial (1.9%) septal defects. Compared to livebirths, this represents a shift toward more severe cardiac lesions, although all comparable categories, including non‐lethal conditions such as atrial septal defect, are more common in stillbirths. Clinical cardiomyopathy was identified as cause of death in 1.2% of stillborns. Cardiomegaly, occurring in 26.7% of all cases and 76.7% of infants born to diabetic mothers, may represent undiagnosed cardiomyopathy and/or may decrease fetal tolerance of hypoxia. In contrast, 78.5% of Turner syndrome infants, all <32 weeks, had small hearts. More attention to cardiac findings can lead to increased understanding of stillbirth causes. Based on our findings, we recommend chromosome studies on all stillbirths and close attention to the heart during second trimester ultrasounds, with chromosome studies offered if CHD is found. Consideration of heart size can result in prenatal identification of infants at risk for stillbirth, particularly large hearts in fetuses of diabetic mothers in the third trimester, which may identify fetal cardiomyopathy before it becomes life‐threatening. © 2014 Wiley Periodicals, Inc.